2012
DOI: 10.4081/jlimnol.2012.e24
|View full text |Cite
|
Sign up to set email alerts
|

Spatial uniformity in depth optima of midges: evidence from sedimentary archives of shallow Alpine and boreal lakes

Abstract: In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In addition, the RDA results ( Table 2) clearly indicated that temperature is the most significant variable explaining chironomid distribution among the mutually measured variables in the Finnish and Polish datasets. Importantly, water depth, which has been found significant in explaining intralake chironomid distributions in Finland (Luoto 2010) and elsewhere (Kurek & Cwynar 2009, Engels et al 2012, Luoto 2012a, 2012b, explained only a minor share of the chironomid community compositions. Therefore, these results demonstrate that the chironomid assemblages closely respond to mean July air temperature in the combined dataset, and consequently justify the development of the East European chironomid-based temperature model.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, the RDA results ( Table 2) clearly indicated that temperature is the most significant variable explaining chironomid distribution among the mutually measured variables in the Finnish and Polish datasets. Importantly, water depth, which has been found significant in explaining intralake chironomid distributions in Finland (Luoto 2010) and elsewhere (Kurek & Cwynar 2009, Engels et al 2012, Luoto 2012a, 2012b, explained only a minor share of the chironomid community compositions. Therefore, these results demonstrate that the chironomid assemblages closely respond to mean July air temperature in the combined dataset, and consequently justify the development of the East European chironomid-based temperature model.…”
Section: Resultsmentioning
confidence: 94%
“…It is known that within one water body the concentration of chironomid head capsules can vary from zero to several thousand per 1 cm 3 of sediments (Kalinkina and Belkina, 2018;Walker et al, 1997) depending on factors such as water depth, rate of sediment accumulation, the hydrological conditions, or anthropogenic influence. Water depth in particular is a major driving factor of chironomid assemblages (Ali et al, 2002;Luoto, 2012;Vemeaux and Aleya, 1998), with depth optima of several species consistent across broad spatial scales . Chironomid remains from the deepest zones of Bolshoe Toko represent an assemblage of elements of profundal necrocenosis (Hofmann, 1971) mixed with secondary components of littoral fauna transported with in-lake hydrological and sedimentary processes into the profundal zone from outside.…”
Section: Factors Explaining the Spatial Chironomid Distributionmentioning
confidence: 99%
“…It is known that even within one water body the concentration of chironomid head capsules may vary from zero to several thousand per 1 cm 3 of sediments (Kalinkina and Belkina, 2018;Walker et al, 1997), depending on the various ecological factors including the water depth, rate of sediment accumulation, the hydrological conditions, or anthropogenic influence. Water depth is a major driving factor of chironomid assemblages in many studies (Ali et al, 2002;Luoto, 2012;Vemeaux and Aleya, 1998) and depth optima of several species prove to be consequent across broad spatial scales (Nazarova et al, 2011). Taphonomy assumes that the assemblage of chironomid remains from the deepest zones of lake represents an assemblage of elements of profundal necrocenosis (Hofmann, 1971) mixed with secondary components of littoral fauna transported Biogeosciences Discuss., https://doi.org/10.5194/bg-2019-146 Manuscript under review for journal Biogeosciences Discussion started: 16 May 2019 c Author(s) 2019.…”
Section: Factors Explaining the Spatial Chironomid Distributionmentioning
confidence: 99%